Why Most Traumatic Brain Injuries are Not Caused by Linear Acceleration but Skull Fractures are - Kleiven, Svein (Frontiers in Bioengineering and Biotechnology, 2013)
Injury statistics have found the most common accident situation to be an oblique impact. An oblique impact will give rise to both linear and rotational head kinematics. The human brain is most sensitive to rotational motion. The bulk modulus of brain tissue is roughly five to six orders of magnitude larger than the shear modulus so that for a given impact it tends to deform predominantly in shear. This gives a large sensitivity of the strain in the brain to rotational loading and a small sensitivity to linear kinematics. Therefore, rotational kinematics should be a better indicator of traumatic brain injury risk than linear acceleration. To illustrate the difference between radial and oblique impacts, perpendicular impacts through the center of gravity of the head and 45o oblique impacts were simulated. It is obvious that substantially higher strain levels in the brain are obtained for an oblique impact, compared to a corresponding perpendicular one, when impacted into the same padding using an identical impact velocity. It was also clearly illustrated that the radial impact causes substantially higher stresses in the skull with an associated higher risk of skull fractures, and traumatic brain injuries secondary to those.